Bloody Mystery After Vomiting - Naser, Maryam; Nasseri, Farbod; Hashemi, Nafiseh (Journal of Ophthalmology and Research, 2020)
Abstract A 71-year-old Asian female was referred to neuro-ophthalmology clinic with a history of redness in the right eye for six months and recent vision loss. There was a history of severe vomiting few months ago. The patient developed red eye following vomiting, which has been treated as conjunctivitis for few months with no improvement. After 6 months she noticed vision loss in the right eye because of CRVO. MRI brain showed carotidcavernous fistula.